PTH-066 Activation of the bile acid receptor, farnesoid-x receptor, maintains gut epithelial cell morphology, possibly via inhibition of myosin light chain kinase expression. (22nd June 2015) - Speight, RA; Davey, T; White, K; Kirby, JA; Mansfield, JC
Abstract : Introduction: By inducing epithelial barrier dysfunction, IBD associated inflammatory cytokines increase the leakiness of the gut mucosa, driving chronic inflammation. 1 Epithelial permeability increases, in part, due to cell-cell junction re-arrangement, mediated by myosin light chain kinase (MLCK). 2 FXR agonism has been shown to maintain the epithelial barrier in a mouse model of colitis. 3 The aim of this study was to assay the effect of FXR agonism on epithelial cell morphology in a human, gut-derived epithelial model of barrier dysfunction. Method: Fully differentiated Caco-2 cells were cultured as a polarised monolayer and treated with TNFα, IFNγ or IL-6 with or without an FXR agonist. At 48 h, transmission electron microscopy was performed to assess for morphological re-arrangement of the cell-cell junction. Two independent researchers, blinded as to intervention, counted the number of morphological re-arrangements in 20 samples, chosen at random. RNA was isolated from IL-6 treated monolayers and the expression of MLCK was measured by RT-PCR (ΔΔCt method). Unpaired t- tests were calculated using Prism version 6.0e. All P values were 2-tailed, and a P value of 0.05 or less was considered significant. Results: FXR agonism reduced the number of epithelial cell-cell junction fissures for monolayers stressed with IFNγ (mean 62.5% to 30%) and IL-6 (mean 69.5% to 42.5%). This was significant in the IFNγ group (p = 0.03), but failed to reach significance in the IL-6 group (p = 0.08). There were no, or few, morphological re-arrangements in control, FXR agonist only or TNFα treated monolayers. Cells stressed with IL-6 demonstrated a significant increase in the relative expression of MLCK (fold increase 435.4). The IL-6 induced upregulation of MLCK was completely abolished by co-treatment with FXR agonist. Conclusion: Evidence is presented to demonstrate that FXR acts to maintain human, gut-derived epithelial cell morphology after stress with IFNγ and IL-6, probably via a mechanism involving the regulation of MLCK expression. FXR agonists are potential therapeutic compounds in the management of IBD. References: Capaldo CT et al . Bioch. Bioph. Acta 2009;1788:864–871 Cunningham KE et al . Ann. N. Y. Acad. Sci . 2012;2058:34–42 Gadaleta RM et al . Gut 2011;60:463–472 Disclosure of interest: None Declared.